Identifikasi Bidang Gelincir Dengan Menggunakan Metode Geolistrik Tahanan Jenis Sebagai Upaya Mitigasi Bencana Tanah Longsor (Studi Kasus : Dusun Payan, Desa Punten, Kota Batu) - Pratiwie, Dessy Lutfiani; Susilo, Adi; Kamali, Ahmad Byan; Dwinanda, Indah Gumilang (Universitas Sultan Ageng Tirtayasa, 2024)
A sliding plane is a layer below the surface that is impermeable. The sliding plane becomes a place where the soil mass experiences movement so that the weathered layer above it experiences landslides following the slope. Payan Hamlet, located in Punten Village, Batu City, which is the research area, is included in a landslide-prone village as evidenced by the recapitulation of BPBD disaster data for Batu City during 2022, 6 landslides occurred. The geoelectric method used in this study is the Wenner configuration. It was used to identify the subsurface condition and interpret the slide plane and direction of the landslide. There are 5 trajectories in this study with 5 m electrode spacing. Based on the results of 2D data processing, the distribution of resistivity values in the research area is diverse. The resistivity value is divided into 3 (three) categories. The low resistivity category with a value of 13 - 51 Ωm is interpreted as a clay layer, the medium resistivity category with a value of 70 - 100 Ωm is interpreted as a tuff layer, and the high resistivity category with a value of 100 - 200 Ωm is interpreted as volcanic breccia. The interpretation of the layer that becomes the sliding field in the research area is the tuff layer with a depth of ± 3.8 - 4m. Based on the results of 2D data processing and calculation of the degree of slope, it can be analysed that the direction of the landslide leads to the southeast side of the research area. Installation of evacuation route signs around the research area is considered as a disaster mitigation effort that can be done